2008
DOI: 10.1080/10911350802171120
|View full text |Cite
|
Sign up to set email alerts
|

Are Women Faculty Just “Worrywarts?” Accounting for Gender Differences in Self-Reported Stress

Abstract: Contrary to notions that faculty women are overly sensitive and over-dramatize their work-life challetiges, quantitative and qualitative data from a large public research university provide contrasting work-life experiences for female and male faculty. Significant gender differences, emphasized by rich description from faculty, are reported in teaching, service, and research responsibilities that contribute to increased levels of stress for women. Specific strategies for creating more equitable and less stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 17 publications
(21 reference statements)
3
32
0
4
Order By: Relevance
“…Women cited a clash between a research career and a family, as well as 'disillusionment with academia' because of its 'low pay, political infighting, and harsh competition for money,'" (Wilson, 2004, p. 7). Further, an investigation by Hart and Cress (2008) revealed women faculty were more likely to indicate committee work was a source of stress and reported they were expected to do more service than their male colleagues and were not rewarded for their work.…”
Section: Work Life Satisfactionmentioning
confidence: 99%
“…Women cited a clash between a research career and a family, as well as 'disillusionment with academia' because of its 'low pay, political infighting, and harsh competition for money,'" (Wilson, 2004, p. 7). Further, an investigation by Hart and Cress (2008) revealed women faculty were more likely to indicate committee work was a source of stress and reported they were expected to do more service than their male colleagues and were not rewarded for their work.…”
Section: Work Life Satisfactionmentioning
confidence: 99%
“…These differences were only partly attributable to differences in job settings, the discrepancies being most marked in universities where proportionately twice as many women as men taught only undergraduate classes (p. 335). Relatedly, Hart and Cress (2008) found that in comparison with male faculty, female faculty actually bear more of the workload. Research shows that female faculty devote more time to teaching than male faculty (Allen 1998;Bellas and Toukoushian 1999), and that service assignments are a heavier burden on female faculty than on male faculty (Hart and Cress 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Relatedly, Hart and Cress (2008) found that in comparison with male faculty, female faculty actually bear more of the workload. Research shows that female faculty devote more time to teaching than male faculty (Allen 1998;Bellas and Toukoushian 1999), and that service assignments are a heavier burden on female faculty than on male faculty (Hart and Cress 2008).…”
Section: Introductionmentioning
confidence: 98%
“…There is also evidence of larger gender gaps in salaries and job satisfaction in economics compared with other math‐intensive fields (Ceci et al ., ; Bandiera, ). The commonly offered reason for the lack of female academics at higher ranks, or delays in the tenure process, is stress related to work–life issues in the areas of teaching, research, service (Hart and Cress, ) and family issues that include pregnancy decisions and caring for children (Ginther and Kahn, ; Ceci et al ., ). Women often teach classes with heavier student loads and spend more time on mentoring and advising responsibilities, which leaves them less time for research.…”
Section: Introductionmentioning
confidence: 99%